2013
DOI: 10.1088/0031-9155/58/4/923
|View full text |Cite
|
Sign up to set email alerts
|

Investigating longitudinal changes in the mechanical properties of MCF-7 cells exposed to paclitaxol using particle tracking microrheology

Abstract: Evidence suggests that compression and shear wave elastography are sensitive to the mechanical property changes occuring in dying cells following chemotherapy, and can hence be used to monitor cancer treatment response. A qualitative and quantitative understanding of the mechanical changes at the cellular level would allow to better infer how these changes affect macroscopic tissue mechanical properties and therefore allow the optimization of elastographic techniques (such as shear wave elastography) for the m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…The adoption of elastography to new clinical applications, such as characterizing highly heterogeneous tumor masses or organs, will likely require the adoption of more complex modeling that accounts for tissue viscoelasticity 25, 26. This is in part due to a tumor's highly heterogeneous microenvironment, which contains stiff elastic regions (e.g., fibrosis, calcifications) as well as soft viscous regions (e.g., blood pools, cystic degeneration areas) with variations at different length-scales 27-29.…”
Section: Principles and Techniques Of Ultrasound Elastographymentioning
confidence: 99%
“…The adoption of elastography to new clinical applications, such as characterizing highly heterogeneous tumor masses or organs, will likely require the adoption of more complex modeling that accounts for tissue viscoelasticity 25, 26. This is in part due to a tumor's highly heterogeneous microenvironment, which contains stiff elastic regions (e.g., fibrosis, calcifications) as well as soft viscous regions (e.g., blood pools, cystic degeneration areas) with variations at different length-scales 27-29.…”
Section: Principles and Techniques Of Ultrasound Elastographymentioning
confidence: 99%
“…Later studies demonstrated the power of PTM for probing cellular microstructure, including the relatively increased stiffness of the interphase nucleus compared to the cytoplasm [101], the spatial uniformity of the viscoelasticity in the cytoplasm of developing Caenorhasbditis elegans embryos [102], the relationship between matrix stiffness and cellular stiffness [103], and the changes in mechanical properties of cancer cells in response to chemotherapy treatment [104]. In these cases, the drag exerted by the fluid on the NP reveals the local elasticity or viscosity.…”
Section: The Utility Of Particle Tracking Analysis In Drug and Genmentioning
confidence: 99%
“…Quantitative ultrasound has also been reported to be able to monitor tissue changes in response to cancer treatment administration (SadeghiNaini et al 2013). Stiffness, as evaluated with ultrasound, could also be an interesting parameter for assessment of treated tissues, because response to therapy is associated with cell death and changes in the biomechanical properties of the tumors (El Kaffas et al 2013). Ultrasound elastography is a relatively recent technique that reflects tissue stiffness.…”
Section: Introductionmentioning
confidence: 99%